Connexin43 Hemichannels Mediate Small Molecule Exchange between Chondrocytes and Matrix in Biomechanically-Stimulated Temporomandibular Joint Cartilage - Zhang, Jing (Osteoarthritis Cartilage, 2014)
OBJECTIVE: Connexin (Cx) 43 hemichannels play a role in mechanotransduction. This study was undertaken in order to determine if Cx43 hemichannels were activated in rat temporomandibular joint (TMJ) chondrocytes under mechanical stimulation. METHODS: Sprague-Dawley rats were stimulated dental-mechanically. Cx43 expression in rat TMJ cartilage was determined with immunohistochemistry and real-time PCR, and Cx43 hemichannel opening was evaluated by the extra- and intracellular levels of prostaglandin E(2) (PGE(2)). Both primary rat chondrocytes and ATDC5 cells were treated with fluid flow shear stress (FFSS) to induce hemichannel opening. The Cx43 expression level was then determined by real-time PCR or western blotting, and the extent of Cx43 hemichannel opening was evaluated by measuring both PGE(2) release and cellular dye uptake. RESULTS: Cx43 expression and intra- and extracellular PGE(2) levels were increased in mechanically-stimulated rat TMJ cartilage compared to the unstimulated control. The FFSS treatment increased Cx43 expression and induced Cx43 hemichannel opening in primary rat chondrocytes and ATDC5 cells indicated by enhanced PGE(2) release and dye uptake. Furthermore, the Cx43 hemichannel opening could be blocked by the addition of 18β-glycyrrhetinic acid, a connexin channel inhibitor, Cx43-targeting siRNA, or by withdrawal of FFSS stimulation. The migration of cytosolic Cx43 protein to the plasma membrane in ATDC5 cells was still significant after 8h post 2-h FFSS treatment, and the Cx43 protein level was still high at 48h which returned to control levels at 72h after treatment. CONCLUSION: Cx43 hemichannels are activated and mediate small molecule exchange between TMJ chondrocytes and matrix under mechanical stimulation.